2012
DOI: 10.1029/2011ja017364
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic instabilities in the lunar wake: ARTEMIS observations

Abstract: The Acceleration, Reconnection, Turbulence and Electrodynamics of the Moon's Interaction with the Sun (ARTEMIS) mission is a new two‐probe lunar mission derived from the Time History of Events and Macroscale Interactions during Substorms (THEMIS) mission. On 13 February 2010, one of the two probes, ARTEMIS P1 (formerly THEMIS‐B), made the first lunar wake flyby of the mission. We present detailed analysis of the electrostatic waves observed on the outbound side of the flyby that were associated with electron b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 62 publications
10
50
0
Order By: Relevance
“…However, for normalised beam speeds which are greater than 2.15, we identify the instability as the electron beamresonant instability, typified by x r / kv dbz . 24 The transition from the electron-acoustic to the electron beam-resonant instabilities is clearly seen in the real frequency curve corresponding to v dbz ¼ 2.15 C h which exhibits the characteristics of both instabilities.…”
Section: Numerical Resultsmentioning
confidence: 92%
“…However, for normalised beam speeds which are greater than 2.15, we identify the instability as the electron beamresonant instability, typified by x r / kv dbz . 24 The transition from the electron-acoustic to the electron beam-resonant instabilities is clearly seen in the real frequency curve corresponding to v dbz ¼ 2.15 C h which exhibits the characteristics of both instabilities.…”
Section: Numerical Resultsmentioning
confidence: 92%
“…2 That the regions with signs of ion-beam disruption lie close to the center of the wake is suggestive, however, since that is where the seeds of the ion-disrupting holes originate in the simulations. It is also where the high-resolution data showed possible signs of slow-moving electron holes, 27 and appears to be the source of an outward-propagating electron beam; 3 electron holes generally increase the parallel electron temperature, and deep ones can appear as beams.…”
Section: Observational Signaturesmentioning
confidence: 96%
“…That could make them easier to detect and characterise, but may also make them more difficult to disentangle from other signal variations. One of the high-resolution observations reported by Tao et al 27 revealed broad-band electrostatic fluctuations at around the ion plasma frequency, for which electron holes were proposed as one possible cause (cf. Ref.…”
Section: Observational Signaturesmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, higher‐frequency, ∼100 Hz whistlers are weakened when the field lines are connected to strong crustal fields, suggesting electron anisotropy caused by surface absorption as a plausible free energy source [ Harada et al , ]. Broadband electrostatic emission is frequently detected on the field lines connected to the Moon or to the lunar wake, as well as inside the wake [ Bale et al , ; Farrell et al , ; Hashimoto et al , ; Nishino et al , ; Tao et al , ; Harada et al , ].…”
Section: Introductionmentioning
confidence: 99%